Toward Identifying Proto-Judaic Cultural Features in Ancient Israel and Judea - Adler, Yonatan (Journal of ancient Judaism, 2025)
The present article examines methodological prospects and pitfalls we face in identifying specific practices prescribed in the Pentateuch and that were adopted as elements within Judaism, which have roots in much earlier Israelite/Judean cultural praxis. Identifying such practices – which we may think of as “proto-Judaic” – is crucial for investigating the degree to which early Judaism manifests the culmination of a long-evolving cultural inheritance reaching back to before the compilation of Pentateuchal texts, versus the degree to which early Judaism reflects fundamentally novel developments following widespread adoption of the Pentateuch as authoritative Torah law. The article examines concrete methodological issues regarding how various types of evidence potentially relevant to identifying proto-Judaic cultural features are to be treated: (1) epigraphic finds; (2) archaeological remains; (3) narratives in Hebrew Bible texts which predate the relevant Pentateuchal texts; and (4) etiological accounts within the Pentateuch itself.